2020
DOI: 10.3390/ani10122217
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance of Escherichia coli Isolated from Conventional, No Antibiotics, and Humane Family Owned Retail Broiler Chicken Meat

Abstract: The use of antibiotics for therapeutic and especially non-therapeutic purposes in livestock farms promotes the development of antibiotic resistance in previously susceptible bacteria through selective pressure. In this work, we examined E. coli isolates using the standard Kirby-Bauer disk diffusion susceptibility protocol and the CLSI standards. Companies selling retail chicken products in Los Angeles, California were grouped into three production groupings—Conventional, No Antibiotics, and Humane Family Owned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…As we understand, the use of antimicrobial agents for therapeutic and especially non-therapeutic purposes for farm animals will promote the incidence of antimicrobial agent resistance through selective pressure. The majority of previous research was conducted on farm animals whose sole purpose was to produce food [42][43][44]. Antimicrobial agents used in animal farms for food production are not intended to promote growth; however, if infectious diseases are not treated promptly, they can negatively impact the productivity and economy of affected businesses.…”
Section: Discussionmentioning
confidence: 99%
“…As we understand, the use of antimicrobial agents for therapeutic and especially non-therapeutic purposes for farm animals will promote the incidence of antimicrobial agent resistance through selective pressure. The majority of previous research was conducted on farm animals whose sole purpose was to produce food [42][43][44]. Antimicrobial agents used in animal farms for food production are not intended to promote growth; however, if infectious diseases are not treated promptly, they can negatively impact the productivity and economy of affected businesses.…”
Section: Discussionmentioning
confidence: 99%
“… Streptomycin, tetracycline, kanamycin [ 144 ] Amoxicillin/clavulanic acid, ampicillin, azithromycin, cefoxitin, ceftiofur, ceftriaxone, chloramphenicol, nalidixic acid, streptomycin, sulfisoxazole, tetracycline, trimethoprim/sulfamethoxazole [ 145 ] Campylobacter spp. Tetracycline [ 146 ] Escherichia coli Ampicillin, cephazolin, streptomycin, tetracycline [ 117 ] Ampicillin, erythromycin [ 134 ] β-lactams [ 147 ] Staphylococcus aureus Clindamycin, oxacillin [ 27 ] Clostridium perfringens Not available Enterococcus spp. Streptomycin, erythromycin [ 148 ] …”
Section: Poultry Production Systems and Amr Bacteriamentioning
confidence: 99%
“…Moreover, a higher prevalence of resistant E. coli to ampicillin, ampicillin-sulbactam, cefazolin, cefoxitin, ceftriaxone, and trimethoprim-sulfamethoxazole was found in conventionally raised turkeys compared to organic and RWA produced ones [ 133 ]. However, Sanchez et al [ 134 ] reported a 56.2% and 60.7% resistance to ampicillin in E. coli when fed conventional and ABF, respectively [ 134 ]. In the Netherlands, extended-spectrum β-lactamase (ESBL)-producing E. coli harboring bla CTX-M-1 and bla CMY-2 genes have been isolated from commercial organic broilers [ 147 ].…”
Section: Poultry Production Systems and Amr Bacteriamentioning
confidence: 99%
“…However, because chickens are much smaller than cows, replacing beef with chicken dramatically exacerbates the negative animal welfare impact of meat consumption (Mathur, 2022). Additionally, chicken production can have other detrimental impacts, including proliferation of antibiotic resistance (Sanchez et al, 2020). Despite significant differences in environmental impacts among the groups, each event footprint fell outside EAT-Lancet's established per-capita planetary boundaries (shown by the black lines in Figures 2A-D, 3A-D).…”
Section: Environmental Footprintmentioning
confidence: 99%